2022
DOI: 10.1007/s12350-020-02448-y
|View full text |Cite
|
Sign up to set email alerts
|

Splenic switch-off as a novel marker for adenosine response in nitrogen-13 ammonia PET myocardial perfusion imaging: Cross-validation against CMR using a hybrid PET/MR device

Abstract: Background No methodology is available to distinguish truly reduced myocardial flow reserve (MFR) in positron emission tomography myocardial perfusion imaging (PET MPI) from seemingly impaired MFR due to inadequate adenosine response. The adenosine-induced splenic switch-off (SSO) sign has been proposed as a potential marker for adequate adenosine response in cardiac magnetic resonance (CMR). We assessed the feasibility of detecting SSO in nitrogen-13 ammonia PET MPI using SSO in CMR as the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It has been shown that the presence of splenic switch-off indicates sufficient adenosine-induced coronary vasodilatation, whereas absence of splenic switch-off is not a reliable marker of failed adenosine response. 38 , 39 This information can be extremely helpful in distinguishing patients with balanced hypoperfusion from non-responders.
Figure 5 A Patient with pronounced splenic switch-off after adenosine stress.
…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the presence of splenic switch-off indicates sufficient adenosine-induced coronary vasodilatation, whereas absence of splenic switch-off is not a reliable marker of failed adenosine response. 38 , 39 This information can be extremely helpful in distinguishing patients with balanced hypoperfusion from non-responders.
Figure 5 A Patient with pronounced splenic switch-off after adenosine stress.
…”
Section: Discussionmentioning
confidence: 99%
“…Patients younger than 18 years, having coronary revascularization, or with contraindications against adenosine/dipyridamole or PET were excluded. 15 Contraindications for the use of adenosine/ dipyridamole were second-or third-degree atrioventricular block, hypotension, bradyarrhythmias, asthma, or hypersensitivity to dipyridamole/adenosine. This study was approved by the Ethics Review Committee of the First Hospital of Shanxi Medical University and a written informed consent was obtained from all patients prior to study participation.…”
Section: Study Population and Designmentioning
confidence: 99%
“…We also did not measure the patients' body fat percentage, lean body mass, or fat distribution. Fourth, we justified the cut-off for CMD based on 15 O-H 2 O rather than 13 N-ammonia. Although 13 N-ammonia and 15 O-water provide similar absolute MBF information over a wide range of blood flows in human, it remains uncertain how these thresholds for hyperemic flows using 15 O-H 2 O compare with 13 N-ammonia.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Splenic switch-off, defined as stress to rest splenic perfusion attenuation in response to A 2A A 2B receptor-mediated vasoconstriction of the afferent splenic arteries during adenosine infusion, 10 has been proposed as an indicator of stress adequacy in cardiac MRI. [11][12][13][14][15] To date, it has been assessed in first-pass perfusion imaging studies since the spleen is commonly captured by the acquired short-axis slices. [11][12][13][14][15] The main disadvantage of using first-pass images for the assessment of splenic switch-off is that stress adequacy is usually determined during the study interpretation once the exam has finished.…”
mentioning
confidence: 99%